United States agricultural stakeholder views and decisions on climate change. (17th May 2017) - Chatrchyan, Allison M.; Erlebacher, Rachel C.; Chaopricha, Nina T.; Chan, Joana; Tobin, Daniel; Allred, Shorna B.
Abstract : Climate change poses unprecedented challenges to agricultural production globally and in the United States; it is both vulnerable to the impacts of a changing climate and a contributor to greenhouse gas emissions. Because farmers need to quickly adapt to reduce their risks and emissions, there is a pressing need to better understand the process by which they make decisions. This complex decision‐making process includes many factors, such as farmers' beliefs; knowledge and capacity to make changes; the information they receive from Extension, industry, and social networks (e.g., family and peers); economics and regulations; and farm‐scale and environmental issues (including personal experience with extreme weather). This study assesses the published literature on U.S. agricultural stakeholder views and decisions on climate change, focusing on farmers and ranchers from different regions. We identify key themes that emerge from the literature on how stakeholder views about extreme weather and climate change relate to decisions about adaptation and mitigation practices. This review finds that although the majority of U.S. farmers believe the climate is changing, many remain skeptical of the issue and uncertain about the anthropogenic causes of climate change. Farmers' climate change mitigation and adaptation decisions also vary widely and are often correlated with belief or other factors such as personal experience with extreme weather, costs of change, or fear of regulation. We conclude with the implications of the research, including the importance of understanding farmers' view and actions and issue framing, and implications for researchers, Extension and policy makers, both nationally and globally. WIREs Clim Change 2017, 8:e469. doi: 10.1002/wcc.469 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Perceptions of Climate Change Abstract : Climate change is causing severe impacts to agriculture globally, and it is essential to understand the views and decisions farmers make about adaptation and mitigation.